Meningkatkan Motivasi Belajar Peserta Didik Kelas VII.2 Pada Mata Pelajaran PPKN Melalui Penggunaan Media Smart Spinner di SMP N 10 Palembang - Afrilya, Nuril; Waluyati, Sri Artati; Saputra, Ardiansyah (Peneliti.net, 2024)
The research was carried out with the author's background found that students who were less interested in learning which students looked unenthusiastically and bored when studying, so the researchers shed to increase the motivation for learning students in PPKN subject through the use of smart media spinner in class VII.2 State Junior High School 10 Palembang. The research was held in the 2023/2024 school year odd trimester. Research on class actions is a research method conducted by writers with julamh, the cycle of 2 cycles each meeting. The method carried out consists of planning, implementation and reflection. This study received the results of students’ motivational data on a cycle of 1 as a criterion for good with a percentage of 55.20% and in the implementation of the 2 cycle which received the increase in the motivation for students with good criteria, percentage of 91.45%. So the research that has been implemented by the author was declared successful.